Legal Certainty The Obligation To Make Administrative Efforts Before Filing A Lawsuit In The Administrative Court - Raya, Bonifacius (Devotion : Journal of Research and Community Service, 2024)
In accordance with the provisions of Article 48 of Law Number 5 of 1986 concerning the State Administrative Court which has been last amended by Law Number 51 of 2009 concerning the Second Amendment of Law Number 5 of 1986 concerning the State Administrative Court ("Peratun Law") which states that not every State Administrative Decision (beschikking) as the object of the State Administrative dispute can be directly sued through the State Administrative Court, because if there are administrative remedies, the state administrative dispute must be resolved first through administrative efforts before being resolved through the State Administrative Court. This research uses a qualitative normative method, which is a process to find a legal rule, legal principles, and legal doctrines to answer the legal issues faced. The result of this study is that Sema No. 1 of 2017 has been affirmed through Perma No. 6 of 2018, thus according to the Court, as long as the administrative effort is intended to file a lawsuit to the PTUN or at least related to the procedural law of the PTUN, the word "can" must be interpreted as "mandatory" to take administrative efforts first. Then the PTUN plays a role in ensuring that law enforcement occurs effectively, by paying attention to the principles of justice and legal certainty that are the basis for every decision taken, and the PTUN plays the role of a court that has the authority to resolve state administrative disputes after the administrative efforts have been passed, in accordance with applicable regulations.